Into the unknown: explorations in development practice - Chambers, Robert (Practical Action Publishing, 2014)
Into the Unknown reflects on the journey of learning, and encourages r eaders to learn from observation, curiosity, critical feedback, play a nd fun. This book will be of interest to development professionals, in cluding academics, students, NGO workers and the staff of internationa l agencies